2017
DOI: 10.13189/eer.2017.050506
|View full text |Cite
|
Sign up to set email alerts
|

Some Features of Surface Air Temperature: A Statistical Viewpoint

Abstract: A climatological study has been done in five weather stations viz Dhuburi, Guwahati, Silchar, Tezpur and Dibrugarh for 45 years , for studying and comparing maximum, minimum and mean temperatures. Coefficient of variation, skewness, kurtosis are also calculated and plotted for comparing the results of the stations. The values of period mean of annual surface air temperature are different at different stations and this value does not show homogeneous distribution in the regions. The pattern of distribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Cluster 5, cluster 6, cluster 3, cluster 1, and cluster 4 have lower RMSE and MAE values than cluster 2, cluster 6, cluster 3, cluster 1, and cluster 4. In comparison to the other clusters, this shows that QM provides reliable results for cluster 5 [48].…”
Section: Resultsmentioning
confidence: 73%
“…Cluster 5, cluster 6, cluster 3, cluster 1, and cluster 4 have lower RMSE and MAE values than cluster 2, cluster 6, cluster 3, cluster 1, and cluster 4. In comparison to the other clusters, this shows that QM provides reliable results for cluster 5 [48].…”
Section: Resultsmentioning
confidence: 73%
“…The monthly behavior of T ave,m , T max,m and T min,m showed that the values were higher in April and May and lower in winter. This is probably due to the minimization of topographic factors during the winter months, the short duration of the day, and the lowest angle at which the sun's rays strike the earth's surface (Dutta et al, 2017). In the agricultural area, the inter-monthly changes of T ave,m , T min,m , T SD,m and T Ra,m , were more significant than in the forest and the urban area.…”
Section: Monthly Air Temperaturementioning
confidence: 93%
“…On the other hand, research by Hashim (1) detected that urbanization, industrialization and house development contributed to the increasing of temperature. Next, study by Dutta et al (28) reveals that location of observation also is one of the factor that can influence the temperature.…”
Section: Factors Influence Temperature Time Seriesmentioning
confidence: 99%